Injuries to the upper extremities in polytrauma: limited effect on outcome more than ten years after injury - a cohort study in 629 patients. (February 2017) - Macke, C.; Winkelmann, M.; Mommsen, P.; Probst, C.; Zelle, B.; Krettek, C.; Zeckey, C.
Abstract : Aims: To analyse the influence of upper extremity trauma on the long-term outcome of polytraumatised patients. Patients and Methods: A total of 629 multiply injured patients were included in a follow-up study at least ten years after injury (mean age 26.5 years, standard deviation 12.4). The extent of the patients' injury was classified using the Injury Severity Score. Outcome was measured using the Hannover Score for Polytrauma Outcome (HASPOC), Short Form (SF)-12, rehabilitation duration, and employment status. Outcomes for patients with and without a fracture of the upper extremity were compared and analysed with regard to specific fracture regions and any additional brachial plexus lesion. Results: In all, 307 multiply-injured patients with and 322 without upper extremity injuries were included in the study. The groups with and without upper limb injuries were similar with respect to demographic data and injury pattern, except for midface trauma. There were no significant differences in the long-term outcome. In patients with brachial plexus lesions there were significantly more who were unemployed, required greater retraining and a worse HASPOC. Conclusion: Injuries to the upper extremities seem to have limited effect on long-term outcome in patients with polytrauma, as long as no injury was caused to the brachial plexus. Cite this article: Bone Joint J 2017;99-B:255–60.